Statistical Analysis of Socio-Economic Factors Affecting Elderly Aged People: A Case Study of District Swabi, Khyber Pakhtunkhwa - Qamruz Zaman; Aman, Saima; Ghazala Sahib, (Dialogue Social Science Review (DSSR), 2024)
Elder people used to have respect, authority and decision making power in the recent past. This dynamics has changed recently. The advancements in technology, industrialization and urbanization have changed the position of elderly people in family and society. They are now vulnerable to many socio-economic challenges that affect them adversely. District Swabi, Khyber Paktunkhwa, is a traditional society where elder people are considered the responsibility of immediate family members. Their economic, social and physical needs are met by their children and grand children. In this study, Multinomial Logistic Regression Model has been applied to explore the socio-economic factors that affect old aged people in district Swabi. The data was collected from different villages of Dist. Swabi through convenient sampling technique. The sample size of the study consists of 300 elderly people of age 60 years or more. Data regarding the education level of elderly people revealed that out of 300 people, 130 were illiterate, 57 had primary education, 63 were matriculates, 32 were intermediate and only 18 had more than intermediate education. The data about health of elderly people included in the sample revealed that approximately 11% were healthy, 24% had joint pain, 21% had blood pressure and 17% were suffering from diabetes (High blood sugar). Investigation of likelihood ratio test showed that the socio-economic variables like family income, advice, respect, disease and the income level of elderly people are significant risk factors for elderly people. The research shows that there is strong association between education and family income of elderly people. Respect by children and satisfaction in life also showed strong association. Strong association was found between satisfaction in life and contacts with friends. The odds ratio showed that elderly males are far more educated than females moreover the study shows that females face more isolation compared to their male counterparts.